2018
DOI: 10.1007/s40258-017-0368-0
|View full text |Cite
|
Sign up to set email alerts
|

A National Budget Impact Analysis of a Specialised Surveillance Programme for Individuals at Very High Risk of Melanoma in Australia

Abstract: Specialised melanoma surveillance is likely to provide substantial cost savings for the Australian healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Uncertainty will be assessed through a scenario, one-way and probabilistic sensitivity analyses. A budget impact analysis similar to our prior study [ 9 ] will estimate the affordability of MSP to the Australian healthcare system and Medicare at scale. Technical details about the economic evaluation will be documented in the Health Economics Analysis Plan (HEAP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainty will be assessed through a scenario, one-way and probabilistic sensitivity analyses. A budget impact analysis similar to our prior study [ 9 ] will estimate the affordability of MSP to the Australian healthcare system and Medicare at scale. Technical details about the economic evaluation will be documented in the Health Economics Analysis Plan (HEAP).…”
Section: Methodsmentioning
confidence: 99%
“…The main drivers of cost-effectiveness were the detection of melanoma at an earlier stage, resulting in less extensive treatment and better quality of life, and fewer excisions for suspicious lesions with specialised surveillance in the hospital outpatient setting (annual mean rate 0.81; 95% CI, 0.72 to 0.91) compared with standard care in the community (2.55; 95% CI, 2.34 to 2.76). A subsequent budget impact analysis indicated that the Australian healthcare system would save AU $22.6 million over 5 years by using specialised melanoma surveillance incorporating TBP, compared with standard care, for people at very high risk of melanoma [ 9 ]. While the evidence has been deemed sufficient to update Australian melanoma clinical practice guidelines [ 10 ], MSP is not listed on the Medicare Benefits Schedule because the Medical Services Advisory Committee advised the Minister for Health that the available evidence in relation to comparative safety, clinical effectiveness and cost-effectiveness was not sufficient to support the public funding of MSP [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mean annual and total healthcare use, costs and QALYs will be quantified for the cohort, preinception and postinception. A budget impact analysis (BIA) will be modelled using best practice methods [23][24][25] over a 5-year time frame. In this BIA, several scenarios will be investigated for the provision of services in a staged implementation in which 50% of eligible Australians will access 3D total body photography in year 1, subsequently rising to 60% in year 2, 70% in year 3, 80% in year 4 and 90% in year 5.…”
Section: Economic Analysismentioning
confidence: 99%
“…Specialised surveillance of individuals at a high risk of developing melanoma appears to be cost effective from preliminary studies showing it can lead to a decrease in yearly healthcare costs in Australia of more than 22 million AUD [ 14 ]. Total-body photography (TBP) is a recommended screening and surveillance method for individuals at a high risk of developing melanoma [ 1 ].…”
Section: This Is New!mentioning
confidence: 99%